Synthesis of Alkyl Aryl Sulfones via Reaction of N-Arylsulfonyl Hydroxyamines with Electron-Deficient Alkenes - Yunhui Bin; Ruimao Hua (Molecules, 2016)
Alkyl aryl sulfones were prepared in high yields via the reaction of N-arylsulfonyl hydroxylamines with electron-deficient alkenes. These reactions have the advantages of simplicity, easily available starting materials and mild reaction conditions.